Anhedonia is associated with suicidal ideation independently of depression: A meta‐analysis. Issue 5 (12th December 2017) - Ducasse, Déborah; Loas, Gwenolé; Dassa, Déborah; Gramaglia, Carla; Zeppegno, Patrizia; Guillaume, Sébastien; Olié, Emilie; Courtet, Philippe
Abstract : Background: Anhedonia is considered a suicide risk factor in patients with major affective disorders. Here, we wanted to quantify the association between anhedonia and current suicidal ideation according to the absence/presence of between‐group differences for depressive scores and psychiatric disorders. Methods: We performed a meta‐analysis of data on studies retrieved from Medline, Web of Science, and PsycINFO from 1965 to 2016 using, among others, the terms (suicid* or depression) and anhedonia. Results: We identified 15 observational case–control studies that investigated the anhedonia differences in individuals with and without current (i.e., within the past week, independently of the lifetime suicidality status) suicidal ideation (defined as thoughts of killing oneself). Overall, 657 subjects with and 6, 690 subjects without current suicidal ideation could be compared. Anhedonia level was higher in the group with current suicidal ideation than in the group without, with a medium effect size (standardized mean difference = 0.57, z  = 5.43, P  < 0.001, 95% confidence interval, CI = 0.37–0.79). The association between anhedonia and current suicidal ideation remained significant when controlling for depression and psychiatric disorders. The anhedonia scales used in the selected studies did not allow investigating consummatory and motivational anhedonia separately. Conclusion: Our major finding is the robust association between anhedonia and current suicidal ideation, independently of depression. This is highly relevant for the clinicians' daily practice and might help improving suicidal risk detection and the development of new therapeutic strategies for suicide prevention.